Complex Pelvic Reconstruction using Patient-Specific Instrumentation and a 3D-Printed Custom Implant following Tumor Resection - Hennessy, David W.; Anderson, Megan E.; Lozano-Calderón, Santiago A. (The Journal of Hip Surgery, 2018)
Resection of a periacetabular sarcoma is a difficult surgical problem due to the complex bony and soft tissue anatomy. The challenge of pelvic tumor resection lies in achieving clear margins while also reconstructing the defect with a durable construct. Limb salvage surgery involving these types of tumors, as well as other tumors of the pelvis, has made great progress recently due to remarkable technological innovation in the field of computer-assisted surgery and custom implant design. In this study, the authors review the case of a 9-year-old child with an osteosarcoma arising from the proximal femur with local spread into the hip joint and a skip metastasis in the ipsilateral acetabulum. They undertook limb-sparing extra-articular resection of the sarcoma with a reconstruction consisting of a 3D-custom printed pelvic implant and a proximal femur extendible prosthesis. The resection of the pelvis was performed with patient-specific cutting guides, rather than computer-assisted navigation. The resection resulted in a clear margin and the patient has had no evidence of local recurrence. These patient-specific guides closely matched the planned resection in terms of orientation in the pelvis, which allowed for straightforward implantation of the custom prosthesis at the time of surgery. The result has been a durable reconstruction that has produced an excellent functional outcome for this patient.
Keywords: 3D-printing; pelvic sarcoma; computer-aided design; orthopaedic oncology; extendible prosthesis